The neuromuscular fatigue in endurance performance, the relevance of the rate of force development - Boccia, G. (8th International Congress Mountain Sport & Health. Updating Study and Research from Laboratory to Field. 7-8 November 2019, Rovereto (TN) - Italy. Programme and Book of Abstracts, 2019)
Muscle fatigue can be defined as an exercise-induced decreased capacity to generate maximal force. Thus, measuring reductions in maximal voluntary contraction force is considered as the most valid and widespread approach to measure muscle fatigue (Place et al., 2010). Strength loss is a common finding after endurance running in ecological race conditions: it increases non-linearly with the duration of exercises and it may vary between 8 and 41% (Place et al., 2010; Giandolini et al., 2016). The decrease in maximal force is usually associated with a reduced capacity to voluntarily activate the knee extensors in maximal contraction and reflect the presence of central fatigue. Central fatigue constitutes an important limitation to performance and is the major cause of the maximal forc e decrease induced by a prolonged whole body exercise such as running (Saldanha et al., 2008). The amount of central fatigue depends on many exercise parameters, such as intensity, duration, and contraction modality, among others. However, it is evident in the literature that central fatigue is overall greater for extreme-duration running (Martin et al., 2010; Temesi et al., 2014) rather than for shorter, more intense bouts like half-marathons (Boccia et al., 2018). Together with decrease in maximal strength, endurance sport races induce a considerable decrease in rate of force development (RFD) of locomotor muscles (Boccia et al., 2016; Boccia et al., 2018). The RFD reflects the ability to rapidly increase muscle force after the onset of an explosive voluntary contraction (Maffiuletti et al., 2016; Rodriguez-Rosell et al., 2017). This is an important feature when the time required to develop maximal force (300 ms or more) is longer than the time available to develop force (Maffiuletti et al., 2016). For example, runners repeatedly cope with the transient of the vertical ground reaction force within the first 100-150 ms of stance (Lieberman et al., 2010), thus the capacity to produce force in brief and fast muscle contractions likely influence running mechanics. The detrimental effects of prolonged exercise on RFD was showed to be related to both central and peripheral fatigue (Boccia et al., 2018). Furthermore, it was shown that the capacity to maintain a rapid force production is important in fatigued states, even though this aspect has received little attention in the literature so far. Nevertheless, if the decrease in RFD during a prolonged running is an epiphenomenon or it is relevant to the final performance is still to be clearly determined.